ESTABLISHMENT OF THE RELATIONSHIP BETWEEN PHYSICO-CHEMICAL INDICATORS OF CHERRY FRUITS DURING STORAGE BY THE CORRELATION PLEYADE METHOD - O. V. Vasylyshyna (Вісник Уманського національного університету садівництва, 2020)
The article shows the relationship between the physicochemical parameters of cherry fruits, pre-treated with polysaccharide compositions, during storage by the method of correlation galaxies. Since cherry fruits spoil quickly, their quality deteriorates after harvest, which leads to microbiological spoilage, weight loss. An important factor in preventing microbiological spoilage of fruits is their proper storage and packaging. The aim of the study was to establish the relationship between the physicochemical parameters of cherry fruits, pre-treated with polysaccharide compositions, before storage by the method of correlation galaxies. The object of study were the fruits of cherries varieties Alpha and Memory Artemenko. For research, the fruits were sprayed with a solution of salicylic acid; chitosan with salicylic acid, dried, removed at the consumer stage of maturity, laid down for storage. Unprocessed fruits took control. Physico-chemical parameters of cherry fruits during storage are interconnected and form one correlation galaxy in which the main indicator is the intensity of respiration. Pre-treatment with a solution of chitosan with salicylic acid had a positive effect on maintaining the quality of cherry fruits. Significant changes during the storage of cherry fruits occurred during the treatment of chitosan fruits with salicylic acid. Strong correlations were found between the intensity of respiration and the activity of the catalase enzyme (r = −0,95 and −0,93) and the content of tannins and dyes (r = −0,94 and −0,91). The calculations made it possible to derive regression equations that allow predicting the activity of catalase and the content of tannins and dyes of cherry fruits knowing the intensity of respiration of fruits during storage.